Policing in Africa - Francis, D. author. aut Link
XII, 219 p.
Keywords: This wide-ranging collection offers fresh insights into a critical factor in development and politics on the African continent. It critically examines and illustrates the centrality of policing in transition societies in Africa, and outlines and assesses the emergence and impact of the diversity of state and non-state policing agencies.